Evaluation of autoantibodies against oxidized LDL and antioxidant status in top soccer and basketball players after 4 months of competition. - Pincemail, J.; Lecomte, J.; Castiau, J.; Collard, E.; Vasankari, T.; Cheramy-Bien, J.; Limet, R.; Defraigne, J. (Free Radical Biology and Medicine, 2000)
Antioxidant status and titers of autoantibodies against oxidized low-density lipoproteins (ox-LDL-Ab) were investigated in top soccer (S; n = 21, age 24.6 +/- 4.3 years) and basketball (B; n 3,000 mIU/ml) in ox-LDL-Ab were found in half the players (12S and 4B) with a maximum reaching 6000 mIU/ml (normal range: 200-600 mIU/ml), showing an in vivo LDL oxidation. There was no correlation between ox-LDL-Ab titers and chlolesterol, LDL cholesterol, or antioxidant levels. Nevertheless, plasma vitamin C concentration was lower in athletes having high levels of ox-LDL-Ab when compared with those with normal levels (8.49 +/- 3.14 mug/ml vs. 10.39 +/- 2.55 mug/ml), but this difference was not statistically significant. In conclusion, our data suggest that potential atherogenic and cardiovascular risks as reflected by high titers in ox-LDL-Ab may exist in some top athletes despite a nonaltered antioxidant status. In: Free Radic Biol Med 2000 Feb 15;28(4):559-565